Quality distortions in vertical relations - Pio Baake; Vanessa von Schlippenbach (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper examines how delivery tariffs and private quality standards are determined in vertical relations that are subject to asymmetric information. We consider an infinitely repeated game where an upstream firm sells a product to a downstream firm. In each period, the firms negotiate a delivery contract comprising the quality of the good as well as a non-linear tariff. Assuming asymmetric information about the actual quality of the product and focusing on incentive compatible contracts, we show that delivery contracts are more efficient the lower the firms' outside options, i.e. the higher their mutual dependency. Buyer power driven by a reduced outside option of the upstream firm enhances the efficiency of vertical relations, while buyer power due to an improved outside option of the downstream firm implies less efficient outcomes.
Keywords: D82; L14; L15; 330; Quality uncertainty; private standards; vertical relations; buyer power; Lieferanten-Kunden-Beziehung; Anreizvertrag; Produktqualität; Asymmetrische Information; Betriebliche Preispolitik; Nachfragemacht; Theorie